Adeno‐associated virus‐vectored influenza vaccine elicits neutralizing and Fcγ receptor‐activating antibodies. Issue 5 (12th March 2020) - Demminger, Daniel E; Walz, Lisa; Dietert, Kristina; Hoffmann, Helen; Planz, Oliver; Gruber, Achim D; von Messling, Veronika; Wolff, Thorsten
Abstract: The current seasonal inactivated influenza vaccine protects only against a narrow range of virus strains as it triggers a dominant antibody response toward the hypervariable hemagglutinin (HA) head region. The discovery of rare broadly protective antibodies against conserved regions in influenza virus proteins has propelled research on distinct antigens and delivery methods to efficiently induce broad immunity toward drifted or shifted virus strains. Here, we report that adeno‐associated virus (AAV) vectors expressing influenza virus HA or chimeric HA protected mice against homologous and heterologous virus challenges. Unexpectedly, immunization even with wild‐type HA induced antibodies recognizing the HA‐stalk and activating FcγR‐dependent responses indicating that AAV‐vectored expression balances HA head‐ and HA stalk‐specific humoral responses. Immunization with AAV‐HA partially protected also ferrets against a harsh virus challenge. Results from this study provide a rationale for further clinical development of AAV vectors as influenza vaccine platform, which could benefit from their approved use in human gene therapy. Synopsis: The study shows that immunization with adeno‐associated virus vectors protects against divergent lethal influenza A virus infections. Protection correlated with induction of antibodies targeting the head and stalk regions of the viral protein HA, and activating FcγR‐dependent responses. Adeno‐associated virus (AAV) vectors expressing viral antigens were studied for the induction of immune responses protecting against challenge infection with influenza A viruses. Immunization of mice with AAV‐vectored HA constructs elicited broadly reactive antibodies recognizing the HA‐head and ‐stalk regions, respectively, and inducing Fcγ receptor‐dependent responses. Immunized mice were protected against lethal homologous or heterologous viral challenges. Intranasal immunization with AAV‐HA elicited protective responses towards a viral challenge also in ferrets. Abstract : The study shows that immunization with adeno‐associated virus vectors protects against divergent lethal influenza A virus infections. Protection correlated with induction of antibodies targeting the head and stalk regions of the viral protein HA, and activating FcγR‐dependent responses.